Ghost Employment di Sektor Publik: Analisis Hukum Pidana dan Perbandingan Internasional - Syaharani, Zevanya Praja (Media Hukum Indonesia (MHI), 2025)
Ghost employment, a phenomenon characterized by the recording of non-existent or inactive employees on public payrolls, represents a significant challenge to governance and public sector accountability. This study aims to analyze the modus operandi, legal implications, causes, and mitigation strategies of ghost employment in Indonesia, with comparative insights from other countries. The research utilizes a descriptive case study approach, drawing on literature review, legal documents, and prior studies to provide a comprehensive understanding of the issue. Findings indicate that ghost employment involves deliberate manipulation of payroll systems, falsification of administrative documents, and collusion among officials, which collectively result in financial losses and undermine public trust. From a legal perspective, such practices constitute embezzlement, document forgery, and corruption under Indonesian law. The study further highlights that weak internal controls, lack of integrated payroll systems, and insufficient audits are key enabling factors for ghost employment. Comparative analysis with countries like Kenya and Tanzania demonstrates that the integration of digital payroll systems, regular audits, and employee training significantly reduces the occurrence of ghost workers. The study recommends a multi-dimensional mitigation strategy for Indonesia that combines legal enforcement, technological integration, and strengthened internal controls to enhance transparency, accountability, and deterrence. This research contributes to the understanding of ghost employment by bridging legal, administrative, and technological perspectives, offering practical guidance for policymakers, auditors, and public sector institutions to prevent, detect, and respond to ghost employment effectively.